Preparation method of high-moisture-retention polyoxyethylene modified polyacrylate gel film
By co-crosslinking polyacrylate with polyethylene oxide and introducing nanomodified montmorillonite and sodium ions, a high-moisture hydrogel is formed, which solves the insufficient performance of existing gel polymer electrolytes in high-performance flexible battery applications and achieves higher ionic conductivity and strength.
Patent Information
- Application Number
- CN202510391799.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-06-17
AI Technical Summary
The existing gel polymer electrolyte based on polyvinyl alcohol is low in high-performance flexible battery applications, poor tensileability and weak water retention ability, which cannot meet the needs of high-performance flexible batteries.
The polyacrylate salt and polyethylene oxide were co-crosslinked by simple hydrothermal method and baking to form a dry film with an interactive network structure, and the nanomodified montmorillonite and electrolyte sodium ions were introduced through the initial crosslinking to form a highly moisturizing hydrogel.
It improves the ionic conductivity and strength of the hydrogel to meet the application needs of high-performance flexible batteries.
Smart Images

Figure CN120157932A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogels, and specifically to a preparation method of a highly moisturizing poly(ethylene oxide)-modified polyacrylate gel film. Background Art
[0002] In recent years, flexible rechargeable metal-based batteries (such as zinc-air batteries, zinc-nickel batteries, lithium batteries, etc.) with advantages such as good flexibility, light weight, small volume, high safety, strong weavability, and low cost have attracted much attention. Among the components of various flexible batteries, the gel polymer electrolyte (GPE), as an ion conductor between electrodes, plays a fundamental role in the discharge-charging process and has a significant impact on the rechargeability, working voltage, lifespan, power density, and safety of the battery.
[0003] GPE is composed of a polymer matrix and a liquid component (usually an alkaline, neutral electrolyte, or ionic liquid), combining the advantages of liquid and solid electrolytes. The liquid component plays an important role in increasing ionic conductivity and interfacial stability, and the polymer matrix provides sufficient mechanical strength and shape flexibility. Therefore, at this stage, GPE is the most promising electrolyte and can be easily adapted to current battery technologies. The liquid component that swells the polymer matrix eliminates the leakage problem and ensures the use of GPE in metal-based batteries. In addition, due to the excellent flexibility and elasticity of the polymer structure, the negative effects caused by the volume effect of the electrodes during battery operation and the short circuit caused by dendrite piercing of the traditional separator can be physically tolerated and resisted; moreover, the gel electrolyte can inhibit the uneven deposition and dendrite formation of the metal on the anode side by providing a stable and uniform electrode / electrolyte interface, greatly improving the cycle life of the metal-based battery. However, for such a core component in flexible batteries, the development of high-performance products has lagged seriously. Currently, traditional GPE based on poly(vinyl alcohol) (PVA) has relatively low ionic conductivity, poor stretchability, and weak water retention ability, far from meeting the applications of high-performance flexible batteries. Some other polymers and compounds, such as poly(acrylic acid) (PAA), sodium polyacrylate (PANa), and polyacrylamide (PAM), have shown excellent water retention ability and great potential in optimizing GPE.
[0004] Based on the above research, the present invention will use a simple hydrothermal method and baking to co-crosslink polyacrylate and poly(ethylene oxide) to form a dry film with an interpenetrating network structure. At the same time, the present invention introduces nano-modified montmorillonite through primary crosslinking to provide more crosslinking sites and introduce electrolyte sodium ions, and the formed hydrogel exhibits stronger ionic conductivity and strength. Summary of the Invention
[0005] The object of the present invention is to provide a preparation method of a highly moisturizing poly(ethylene oxide)-modified polyacrylate gel film to solve the problems raised in the above-mentioned background art.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A preparation method of a highly moisturizing poly(ethylene oxide)-modified polyacrylate gel film, and the preparation method is as follows:
[0008] S1. Under the conditions of a cold water bath and strong magnetic stirring, slowly drop the sodium hydroxide solution into acrylic acid and continue stirring to obtain a neutralized acrylate solution, then add ammonium persulfate and N,N'-methylenebisacrylamide and continue stirring for 0.5 - 1 h, and perform primary cross-linking at 50 - 65 °C for 0.5 - 2 h to obtain a pre-cross-linked solution;
[0009] S2. Ultrasonically disperse the modified nano-montmorillonite in deionized water to obtain a uniformly dispersed modified montmorillonite dispersion liquid, and slowly add the modified montmorillonite solution to the pre-cross-linked solution in step S1 to obtain a reaction solution;
[0010] S3. Dissolve poly(ethylene oxide) in deionized water to obtain an aqueous poly(ethylene oxide) solution, slowly add the aqueous poly(ethylene oxide) solution to the reaction solution in step S2 and stir for 0.5 - 1 h to obtain a mixed solution, add the mixed solution to a mold, perform secondary cross-linking at 70 - 85 °C, and dry at the secondary cross-linking temperature to obtain a dry film;
[0011] S4. Immerse the dry film obtained in step S3 in a sodium chloride solution for 6 - 24 h to obtain a highly moisturizing poly(ethylene oxide)-modified polyacrylate gel film.
[0012] Further, in step S1, the concentration of the sodium hydroxide solution is 5 - 10 mol / L, and the molar ratio of sodium hydroxide to acrylic acid is 1:(1 - 1.1).
[0013] Further, in step S1, the mass ratio of N,N'-methylenebisacrylamide to acrylic acid is 1:(100 - 200), and the mass ratio of ammonium persulfate to N,N'-methylenebisacrylamide is 1:(4 - 5).
[0014] Further, in step S2, the mass ratio of the modified nano-montmorillonite, deionized water to acrylic acid in step S1 in the modified nano-montmorillonite dispersion liquid is 1:(20 - 30):(15 - 20).
[0015] Further, in step S3, the mass ratio of poly(ethylene oxide), deionized water to polyacrylic acid in step S1 in the poly(ethylene oxide) solution is 1:(30 - 50):(12.5 - 25).
[0016] Further, the concentration of the sodium chloride solution in the step S4 is 1-3 mol / L.
[0017] Further, the preparation method of the modified nano-montmorillonite in the step S2 includes the following steps:
[0018] S101. Ultrasonically disperse the nano-montmorillonite into hydrogen peroxide with a mass fraction of 30% and soak for 1-2 h;
[0019] S102. Centrifuge and filter the nano-montmorillonite treated with hydrogen peroxide in the step S101, wash it with sufficient deionized water, and then heat it at 200-300 °C for 0.5-3 h;
[0020] S103. Ultrasonically disperse the heated nano-montmorillonite in the step S102 into a sodium carbonate solution, then centrifuge and filter, and wash the filtered product with 0.1 mol / L hydrochloric acid until neutral to obtain the modified nano-montmorillonite.
[0021] Further, the particle size of the nano-montmorillonite in the step S101 is between 20-50 nm, and the mass ratio between the nano-montmorillonite and hydrogen peroxide is 1:(20-50).
[0022] Further, the mass ratio between sodium carbonate, the heated nano-montmorillonite and deionized water in the step S103 is 1:(0.5-2):(15-20).
[0023] Compared with the prior art, the beneficial effects of the present invention are:
[0024] 1. In the present invention, by setting two cross-linking processes, after the first cross-linking, the modified nano-montmorillonite is added. The modified nano-montmorillonite is embedded into the network formed by the primary cross-linking, forming more cross-linking sites, facilitating the subsequent cross-linking between polyethylene oxide and acrylic acid chains, forming an interpenetrating network, and improving the strength of the formed hydrogel;
[0025] 2. In the present invention, the nano-montmorillonite is added through modification. The modified nano-montmorillonite can be evenly embedded into the network formed by acrylate. The modified nano-montmorillonite is loaded with a large amount of sodium ions and enters before the hydrogel is completely polymerized, improving the overall ionic conductivity of the hydrogel. Description of the Drawings
[0026] Figure 1 is the process flow chart for preparing the high-moisture polyethylene oxide-modified polyacrylate gel film of the present invention;
[0027] Figure 2 is the process flow chart for preparing the modified nano-montmorillonite in the present invention;
[0028] Figure 3This is the electron microscope image of the highly moisturizing polyethylene oxide-modified polyacrylate gel film prepared in Example 1 of the present invention. Detailed implementation mode
[0029] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0030] Please refer to Figures 1 to 3 , the present invention provides:
[0031] Example 1
[0032] A preparation method of a highly moisturizing polyethylene oxide-modified polyacrylate gel film, and the preparation method is as follows:
[0033] S1. Under the conditions of cold water bath and strong magnetic stirring, slowly drop 13 ml of sodium hydroxide solution with a concentration of 8 mol / L into 7.2 g of acrylic acid and continue to stir to obtain a neutralized acrylate solution. Then add 60 mg of ammonium persulfate and 13 mg of N,N'-methylenebisacrylamide and continue to stir for 0.8 h, and perform primary crosslinking at 60 °C for 1.5 h to obtain a pre-crosslinked solution;
[0034] S2. Ultrasonically disperse 0.45 g of modified nano-montmorillonite into 11.25 g of deionized water to obtain a uniformly dispersed modified montmorillonite dispersion solution, and slowly add the modified montmorillonite solution into the pre-crosslinked solution in step S1 to obtain a reaction solution;
[0035] S3. Dissolve 0.5 g of polyethylene oxide in 18 g of deionized water to obtain a polyethylene oxide aqueous solution, slowly add the polyethylene oxide aqueous solution into the reaction solution in step S2 and stir for 0.8 h to obtain a mixed solution, add the mixed solution into a mold, perform secondary crosslinking at 80 °C, and dry at the secondary crosslinking temperature to obtain a dry film;
[0036] S4. Immerse the dry film obtained in step S3 in a sodium chloride solution with a concentration of 2 mol / L for 18 h to obtain a highly moisturizing polyethylene oxide-modified polyacrylate gel film.
[0037] The preparation method of the above-mentioned modified nano-montmorillonite includes the following steps:
[0038] S101. Ultrasonically disperse 0.84 g of nano-montmorillonite with a particle size of 30 nm into 28 g of hydrogen peroxide with a mass fraction of 30% and soak for 1.4 h;
[0039] S102. Centrifuge and filter the nano-montmorillonite treated with hydrogen peroxide in step S101, wash it with sufficient deionized water, and then heat it at 220 °C for 1.5 h;
[0040] S103. Ultrasonically disperse 0.78 g of the heated nano-montmorillonite in step S102 into 14.1 g of sodium carbonate solution containing 0.75 g of sodium carbonate, then centrifuge and filter. Wash the filtered product with 0.1 mol / L hydrochloric acid until neutral to obtain modified nano-montmorillonite.
[0041] Example 2
[0042] A preparation method of a highly moisturizing polyethylene oxide modified polyacrylate gel film, and the preparation method is as follows:
[0043] S1. Under the conditions of a cold water bath and strong magnetic stirring, slowly drop 20 ml of a 5 mol / L sodium hydroxide solution into 7.2 g of acrylic acid and continue stirring to obtain a neutralized acrylate solution. Then add 72 mg of ammonium persulfate and 18 mg of N,N'-methylenebisacrylamide and continue stirring for 0.5 h. Conduct primary cross-linking at 50 °C for 0.5 h to obtain a pre-cross-linked solution;
[0044] S2. Ultrasonically disperse 0.48 g of the modified nano-montmorillonite in 9.6 g of deionized water to obtain a uniformly dispersed modified montmorillonite dispersion liquid. Slowly add the modified montmorillonite solution to the pre-cross-linked solution in step S1 to obtain a reaction solution;
[0045] S3. Dissolve 0.576 g of polyethylene oxide in 17.28 g of deionized water to obtain a polyethylene oxide aqueous solution. Slowly add the polyethylene oxide aqueous solution to the reaction solution in step S2 and stir for 0.5 h to obtain a mixed solution. Add the mixed solution to a mold, conduct secondary cross-linking at 70 °C, and dry it at the secondary cross-linking temperature to obtain a dry film;
[0046] S4. Immerse the dry film obtained in step S3 in a 1 mol / L sodium chloride solution for 6 h to obtain a highly moisturizing polyethylene oxide modified polyacrylate gel film.
[0047] The preparation method of the above-mentioned modified nano-montmorillonite includes the following steps:
[0048] S101. Ultrasonically disperse 0.65 g of nano-montmorillonite with a particle size of 20 nm in 13 g of 30% hydrogen peroxide by mass and soak for 1 h;
[0049] S102. Centrifuge and filter the nano-montmorillonite treated with hydrogen peroxide in step S101, wash it with sufficient deionized water, and then heat it at 200 °C for 0.5 h;
[0050] S103. Ultrasonically disperse 0.59 g of heated nano-montmorillonite in step S102 into 8.85 g of sodium carbonate solution, where the mass of sodium carbonate in the sodium carbonate solution is 0.295 g. Then, centrifuge and filter, and wash the filtered product with 0.1 mol / L hydrochloric acid until neutral to obtain modified nano-montmorillonite.
[0051] Example 3
[0052] A preparation method of a highly moisturizing polyethylene oxide-modified polyacrylate gel film, and the preparation method is as follows:
[0053] S1. Under the conditions of a cold water bath and strong magnetic stirring, slowly drop 11 ml of 10 mol / L sodium hydroxide solution into 7.2 g of acrylic acid and continue stirring to obtain a neutralized acrylate solution. Then, add 36 mg of ammonium persulfate and 7.2 mg of N,N'-methylenebisacrylamide and continue stirring for 1 h, and crosslink once at 65 °C for 2 h to obtain a pre-crosslinked solution;
[0054] S2. Ultrasonically disperse 0.36 g of modified nano-montmorillonite in 10.8 g of deionized water to obtain a uniformly dispersed modified montmorillonite dispersion liquid, and slowly add the modified montmorillonite solution to the pre-crosslinked solution in step S1 to obtain a reaction solution;
[0055] S3. Dissolve 0.288 g of polyethylene oxide in 14.4 g of deionized water to obtain a polyethylene oxide aqueous solution, slowly add the polyethylene oxide aqueous solution to the reaction solution in step S2 and stir for 1 h to obtain a mixed solution, add the mixed solution to a mold, perform secondary crosslinking at 85 °C, and dry at the secondary crosslinking temperature to obtain a dry film;
[0056] S4. Immerse the dry film obtained in step S3 in a 3 mol / L sodium chloride solution for 24 h to obtain a highly moisturizing polyethylene oxide-modified polyacrylate gel film.
[0057] The preparation method of the above-mentioned modified nano-montmorillonite includes the following steps:
[0058] S101. Ultrasonically disperse 0.82 g of nano-montmorillonite with a particle size of 50 nm in 41 g of 30% by mass hydrogen peroxide solution and soak for 2 h;
[0059] S102. Centrifuge and filter the nano-montmorillonite treated with hydrogen peroxide in step S101, wash with sufficient deionized water, and then heat at 300 °C for 3 h;
[0060] S103. Ultrasonically disperse the heat-treated nano-montmorillonite in step S102 into 16.4 g of sodium carbonate solution, where the mass of sodium carbonate in the sodium carbonate solution is 1.64 g. Then, centrifuge and filter, and wash the filtered product with 0.1 mol / L hydrochloric acid until neutral to obtain modified nano-montmorillonite.
[0061] Example 4
[0062] A preparation method of a highly moisturizing polyethylene oxide-modified polyacrylate gel film, and the preparation method is as follows:
[0063] S1. Slowly drip 13 ml of 8 mol / L sodium hydroxide solution into 7.2 g of acrylic acid under a cold water bath and strong magnetic stirring conditions, and continue stirring to obtain a neutralized acrylate solution. Then, add 60 mg of ammonium persulfate and 13 mg of N,N'-methylenebisacrylamide, and continue stirring for 0.8 h. Crosslink once at 55 °C for 2 h to obtain a pre-crosslinked solution;
[0064] S2. Ultrasonically disperse 0.36 g of modified nano-montmorillonite in 9 g of deionized water to obtain a uniformly dispersed modified montmorillonite dispersion. Slowly add the modified montmorillonite solution to the pre-crosslinked solution in step S1 to obtain a reaction solution;
[0065] S3. Dissolve 0.32 g of polyethylene oxide in deionized water to obtain a polyethylene oxide aqueous solution. Slowly add the polyethylene oxide aqueous solution to the reaction solution in step S2, stir for 0.7 h to obtain a mixed solution, add the mixed solution to a mold, perform secondary crosslinking at 70 °C, and dry at the secondary crosslinking temperature to obtain a dry film;
[0066] S4. Immerse the dry film obtained in step S3 in a 3 mol / L sodium chloride solution for 22 h to obtain a highly moisturizing polyethylene oxide-modified polyacrylate gel film.
[0067] The preparation method of the above-mentioned modified nano-montmorillonite includes the following steps:
[0068] S101. Ultrasonically disperse 0.56 g of nano-montmorillonite with a particle size of 20 nm in 19.6 g of 30% hydrogen peroxide solution and soak for 1.2 h;
[0069] S102. Centrifuge and filter the nano-montmorillonite treated with hydrogen peroxide in step S101, wash with sufficient deionized water, and then heat at 250 °C for 2.5 h;
[0070] S103. Ultrasonically disperse the heat-treated nano-montmorillonite in step S102 into 11.2 g of sodium carbonate solution, where the mass of sodium carbonate in the sodium carbonate solution is 0.61 h. Then, centrifuge and filter, and wash the filtered product with 0.1 mol / L hydrochloric acid until neutral to obtain modified nano-montmorillonite. It should be noted that there seems to be a mistake in the original text where "the mass of sodium carbonate in the sodium carbonate solution is 0.61h" should probably be a correct value like 0.61g. This translation is based on the provided text with this possible error maintained.
[0071] Comparative Example 1
[0072] The difference between Comparative Example 1 and Example 1 is that during the one - stage cross - linking process in Step S1, the reaction solution contains acrylic acid, ammonium persulfate, N,N'-methylenebisacrylamide, modified nano - montmorillonite, and polyethylene oxide solution, and cross - linking is directly carried out at 80°C to form a dry film.
[0073] Comparative Example 2
[0074] The difference between Comparative Example 2 and Example 1 is that Step S103 is omitted, thus canceling the treatment process of montmorillonite in sodium carbonate solution, and the remaining steps are exactly the same as those in Example 1.
[0075] Comparative Example 3
[0076] The difference between Comparative Example 3 and Example 1 is that the addition of modified nano - montmorillonite is completely canceled, and the remaining steps are exactly the same as those in Example 1.
[0077] Comparative Example 4
[0078] The difference between Comparative Example 4 and Example 1 is that Step S101 is omitted, thus canceling the treatment process of montmorillonite in hydrogen peroxide.
[0079] The hydrogels prepared in the above Examples 1 - 4 and Comparative Examples 1 - 4 were tested for tensile strength and ionic conductivity;
[0080] The test method for ionic conductivity is as follows: A hydrogel with a certain thickness (T) is cut into strips with a width of 2.5 cm (W) and a length of 7 cm. The two ends are wrapped with copper foil, and the length of the gel exposed between the copper foils is 5 cm (L). Then, a stainless - steel electrode clamp is clamped on the copper foil for testing. The frequency range is 0.01 HZ - 106 HZ. The impedance values at different frequencies are measured. By analyzing the impedance spectrum, the resistance value of the hydrogel can be obtained. According to the ionic conductivity formula σ = L / A*R (where L represents the distance between the stainless - steel electrodes (i.e., the length of the gel exposed between the copper foils), A is the cross - sectional area of the polymer gel electrolyte (A = T*W, the cross - sectional area is the product of the gel thickness and width), and R is the resistance of the polymer gel electrolyte), the ionic conductivity of the gel can be calculated;
[0081] The tensile strength test was carried out with reference to the standard of GB / T 16491 - 2008;
[0082] The specific test results are shown in Table 1 below:
[0083] Table 1: Test results of tensile strength and ionic conductivity of hydrogels prepared in Examples 1 - 4 and Comparative Examples 1 - 4
[0084] Ionic conductivity (mS / cm) Tensile strength (MPa) Example 1 364 1.21 Example 2 325 1.07 Example 3 351 1.12 Example 4 347 1.19 Comparative Example 1 309 0.88 Comparative Example 2 285 1.12 Comparative Example 3 279 0.76 Comparative Example 4 345 0.92
[0085] From the data of Example 1 and Comparative Example 1 in Table 1 above, it can be seen that in the present invention, by means of two cross-linking forms, montmorillonite is added into the incompletely cross-linked network of acrylic acid, which is beneficial to the formation of an interpenetrating network of polyethylene oxide in the acrylic acid network later, and the formed hydrogel is uniform and has high strength; from the comparison between Comparative Example 4 and Example 1, it can be seen that when the treatment of montmorillonite with hydrogen peroxide is lacking, the tensile strength of the prepared hydrogel decreases significantly; by comparing Example 1 and Comparative Example 2, it can be seen that the ionic conductivity of the hydrogel decreases significantly, and introducing sodium ions into montmorillonite effectively improves the overall conductivity of the material.
[0086] Figure 3 This is the electron microscope image of the hydrogel prepared in Example 1 of the present invention. Through Figure 3 it can be seen that the surface pores of the hydrogel prepared in the present invention are uniform and the cross-linking effect of the hydrogel is excellent.
[0087] Although the embodiments of the present invention have been shown and described, those of ordinary skill in the art can understand that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a highly moisturizing polyethylene oxide modified polyacrylic acid salt gel film, characterized in that: The preparation method is: S1. Slowly drip sodium hydroxide solution into acrylic acid under strong magnetic stirring in a cold water bath and continue stirring to obtain a neutralized acrylate solution, then add ammonium persulfate and N,N'-methylenebisacrylamide and continue stirring for 0.5-1h, and crosslink once at 50-65°C for 0.5-2h to obtain a pre-crosslinked solution; S2, ultrasonically dispersing the modified nano-montmorillonite in deionized water to obtain a uniformly dispersed modified montmorillonite dispersion, and slowly adding the modified montmorillonite solution to the pre-crosslinking solution in step S1 to obtain a reaction solution; S3, dissolving polyethylene oxide in deionized water to obtain a polyethylene oxide aqueous solution, slowly adding the polyethylene oxide aqueous solution to the reaction solution in step S2, stirring for 0.5-1h to obtain a mixed solution, adding the mixed solution to a mold, performing secondary crosslinking at 70-85° C., and baking at the secondary crosslinking temperature to obtain a dry film; S4, soaking the dry film obtained in step S3 in a sodium chloride solution for 6-24 hours to obtain a highly moisturizing polyethylene oxide modified polyacrylic acid salt gel film.
2. The method for preparing the highly moisturizing polyethylene oxide modified polyacrylic acid salt gel film according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in step S1 is 5-10 mol / L, and the molar ratio of sodium hydroxide to acrylic acid is 1:(1-1.1).
3. The method for preparing the highly moisturizing polyethylene oxide modified polyacrylic acid salt gel film according to claim 1, characterized in that: In the step S1, the mass ratio of N,N'-methylenebisacrylamide to acrylic acid is 1:(100-200), and the mass ratio of ammonium persulfate to N,N'-methylenebisacrylamide is 1:(4-5).
4. The method for preparing the highly moisturizing polyethylene oxide modified polyacrylate gel film according to claim 1, characterized in that: The mass ratio of the modified nano-montmorillonite in the modified nano-montmorillonite dispersion in step S2 to the deionized water and the acrylic acid in step S1 is 1:(20-30):(15-20).
5. The method for preparing the highly moisturizing polyethylene oxide modified polyacrylic acid salt gel film according to claim 1, characterized in that: The mass ratio of the polyethylene oxide and deionized water in the polyethylene oxide solution in step S3 to the polyacrylic acid in step S1 is 1:(30-50):(12.5-25).
6. The method for preparing the highly moisturizing polyethylene oxide modified polyacrylic acid salt gel film according to claim 1, characterized in that: The concentration of the sodium chloride solution in step S4 is 1-3 mol / L.
7. The method for preparing the highly moisturizing polyethylene oxide modified polyacrylate gel film according to claim 1, characterized in that: The preparation method of modified nano-montmorillonite in step S2 comprises the following steps: S101, ultrasonically dispersing the nano-montmorillonite in 30% by mass hydrogen peroxide and soaking for 1-2 hours; S102, centrifugally filtering the nano-montmorillonite treated with hydrogen peroxide in step S101, washing it with a sufficient amount of deionized water, and then heating it at 200-300° C. for 0.5-3 h; S103, ultrasonically dispersing the heated nano-montmorillonite in step S102 into a sodium carbonate solution, and then centrifugally filtering the filtered product, washing it with 0.1 mol / L hydrochloric acid until it is neutral, to obtain modified nano-montmorillonite.
8. The method for preparing the highly moisturizing polyethylene oxide modified polyacrylic acid salt gel film according to claim 7, characterized in that: In the step S101, the particle size of the nano-montmorillonite is between 20-50 nm, and the mass ratio of the nano-montmorillonite to the hydrogen peroxide is 1:(20-50).
9. The method for preparing the highly moisturizing polyethylene oxide modified polyacrylic acid salt gel film according to claim 7, characterized in that: In step S103, the mass ratio of sodium carbonate, heated nano-montmorillonite and deionized water is 1:(0.5-2):(15-20).
Citation Information
Cited By
Preparation method and application of pH responsive hydrogel
CN120329571A